Shortcircuiting Death: The Ending of "Changing Places" and the Death of the Novel - Bárbara María Arizti Martín (Miscelánea: A Journal of English and American Studies, 1996)
According to Peter Brooks we read moved by our desire for the end, for the recognition which is the moment of the death of the reader in the text, and a substitue for our desire for death and dissolution. The experimental “non-ending” of David Lodge’s Changing Places frustrates our expectations by putting an end to the reading activity, but not to our desire for the end. The present paper focuses on the implications of Lodge’s decision to end his novel unexpectedly in the light of the ambiguous relationship between realism and postmodernism.